Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1371/journal.pone.0059730
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Autonomic Nervous System Response to Anxiety in Children with Autism Spectrum Disorders

Abstract: Assessment of anxiety symptoms in autism spectrum disorders (ASD) is a challenging task due to the symptom overlap between the two conditions as well as the difficulties in communication and awareness of emotions in ASD. This motivates the development of a physiological marker of anxiety in ASD that is independent of language and does not require observation of overt behaviour. In this study, we investigated the feasibility of using indicators of autonomic nervous system (ANS) activity for this purpose. Specia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
143
1
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 160 publications
(158 citation statements)
references
References 44 publications
(52 reference statements)
7
143
1
1
Order By: Relevance
“…We had hoped to use heart rate as an index of anxiety, as nervous children may have higher heart rates. 26, 27 This association may have been obscured by the association between obesity or poor lifestyle habits with higher heart rates. 28, 29 …”
Section: Discussionmentioning
confidence: 99%
“…We had hoped to use heart rate as an index of anxiety, as nervous children may have higher heart rates. 26, 27 This association may have been obscured by the association between obesity or poor lifestyle habits with higher heart rates. 28, 29 …”
Section: Discussionmentioning
confidence: 99%
“…Findings pertaining to autonomic system arousal also suggest heightened physiological activity. For example, Kushki et al [40▪] reported sympathetic overarousal and reduced parasympathetic tone in children with ASD who were completing a Stroop task.…”
Section: Risk Factors and Correlates Of Anxiety In Autism Spectrum DImentioning
confidence: 99%
“…EDRs can be interpreted as measures of physiological and psychological arousal, but they can be indicative of both negative and positive stimuli [89]. In clinical rehabilitation, electrodermal measurements may serve as a complementary access pathway to a motor-based switch [91] or brain-computer interface [92], an indicator of autonomic nervous system response to anxiety in children with autism spectrum disorders [93], and a quantitative measure of motor imagery abilities in individuals with spinal cord injuries [94], among other possibilities.…”
Section: Current Practicementioning
confidence: 99%